Methodical instructions for conducting practical classes in the discipline on "Human resource Management and organization behavior" - Shmatko, Nataliia (Національний технічний університет "Харківський політехнічний інститут", 2023)
Practical lesson, which students of the 073 "Management" specialty are to be completed by the curriculum, should contribute to the consolidation and deepening of knowledge, skills and abilities in the "HUMAN RESOURCE MANAGEMENT AND ORGANIZATIONAL BEHAVIOR" discipline acquired during the course of study. Writing and understanding cases is an important stage of studying an academic discipline. The student must learn the necessary skills of research work, master the methods of analysis, information processing, generalization of the theoretical and practical bases of the activity of the object of research, deepen, expand and consolidate knowledge on the chosen topic. The cases the results of scientific research conducted by the student independently. In it, the student must show the ability to competently and reasonedly highlight his own opinions, substantiate proposals, correctly and freely use both generally accepted economic and professional terminology. Preparation of the cases aimed at substantiating the proposals on the researched problems.
Keywords: methodical instructions; practical classes; human resource management; organization behavior; management; personnel management